2015
DOI: 10.1016/j.healthplace.2014.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood and dwelling characteristics associated with the self-reported adverse health effects of heat in most deprived urban areas: A cross-sectional study in 9 cities

Abstract: Dwelling and neighbourhood characteristics associated with the prevalence of self-reported heat-induced adverse health effects are not well known. We interviewed 3485 people in the most disadvantaged neighbourhoods of the nine largest cities in Québec, Canada. The prevalence of heat-induced adverse health effects was 46%, out of which one fourth led to medical consultation. Multivariate analyses showed that dissatisfaction with the summer dwelling temperature, which refers to home heat exposure, and perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…Self-rated health questions are widely used in the health sciences and other fields because, over decades of research, they have been found to be strong correlates of clinical conditions (Lee 2015) and have been used in assessments of heat vulnerability (Belanger et al 2015).…”
Section: Microscale Lst: Master Flight and Data Processingmentioning
confidence: 99%
“…Self-rated health questions are widely used in the health sciences and other fields because, over decades of research, they have been found to be strong correlates of clinical conditions (Lee 2015) and have been used in assessments of heat vulnerability (Belanger et al 2015).…”
Section: Microscale Lst: Master Flight and Data Processingmentioning
confidence: 99%
“…In total, 3,485 people were interviewed from December 21, 2010, to December 20, 2011. In the study, these respondents lived in areas located for the most part in intra-urban heat islands (66 %) or less than 50 m from a heat island (32 %) (Bélanger et al 2015). Data was collected by means of a pre-tested questionnaire (basically closed-ended questions) prepared from a review of the literature on health and climate change and several similar questionnaires in regular use in Canada by statistical agencies.…”
Section: Studymentioning
confidence: 99%
“…In particular, this study suggests that automated phone warning systems with specific guidelines help improve the knowledge and behaviours of the most vulnerable people to heat and relieve pressure on the health care system during heat episodes. Two Canadian studies noted that medical consultations during or after heat waves concerned between 10% and 12% of the adults [8,46]. These systems can therefore be a useful component of heat wave emergency plans.…”
Section: Discussionmentioning
confidence: 99%
“…Heat waves are an important public health issue as they lead to increased mortality, hospitalizations, and morbidity [2,3,4,5,6]. The elderly and chronically ill are particularly vulnerable to this weather hazard [6,7], and their vulnerability is accentuated by certain housing and neighbourhood characteristics such as the unavailability of residential air conditioning and lack of green space in the surrounding environment [8,9]. In addition to health concerns, heat waves have also negative impacts on different aspects of the ecological and social systems such as an increase in energy consumption, bushfire occurrences, and crop damage risks, as well as the degradation of water quality and availability [10].…”
Section: Introductionmentioning
confidence: 99%